2016
DOI: 10.1590/0103-9016-2015-0374
|View full text |Cite
|
Sign up to set email alerts
|

Crop losses in Brazilian cassava varieties induced by the Cassava common mosaic virus

Abstract: Despite the widespread distribution of the Cassava common mosaic virus (CsCMV) in Brazil, little is known about the losses it causes in yield. The effect of CsCMV on different va-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
1
26
1
Order By: Relevance
“…This work highlights the importance of CsCMV early detection in cassava crops in the NEA region of Argentina. Although cassava common mosaic disease (CCMD) has been considered to be of minor importance, current studies indicate it can be associated with up to 30% yield losses in cassava (Venturini et al ., ). The study here reports an incidence of up to 85.2% of CsCMV in the NEA region, comparable to the 96% incidence reported in the neighbouring Brazilian state of Paraná (Silva et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This work highlights the importance of CsCMV early detection in cassava crops in the NEA region of Argentina. Although cassava common mosaic disease (CCMD) has been considered to be of minor importance, current studies indicate it can be associated with up to 30% yield losses in cassava (Venturini et al ., ). The study here reports an incidence of up to 85.2% of CsCMV in the NEA region, comparable to the 96% incidence reported in the neighbouring Brazilian state of Paraná (Silva et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The affected plants develop mosaic and chlorosis in leaves, with increased severity in the subtropical zones of South America due to the prolonged cold periods (Calvert et al ., ). The effects on reduction in root yield caused by CsCMV can be from 30% to 60% (Costa & Kitajima, ; Venturini et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Cassava-CsCMV compatible viral infection causes 30-60% yield reduction of cassava roots (Costa and Kitajima 1972; Venturini el al. 2016; Zanini et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since cassava is vegetatively propagated, its yield is greatly restrained by viral diseases (Legg et al 2015). Among all reported cassava-infecting potexviruses (Lozano et al 2017), Cassava common mosaic virus (CsCMV) has been identified as the only one able to cause disease in single infection and to produce significant yield losses (Costa and Kitajima 1972; Venturini et al 2016; Zanini et al 2020). This pathogen has been detected infecting cassava crops in South America (Calvert et al 2012; Chaparro-Martinez and Trujillo-Pinto 2003; Silva et al 2011; Fernandez et al 2017; Zanini et al 2018) and recently in China (Tuo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation